Coming to Terms with Knowledge Management in Telehealth. (27th November 2016) - Standing, Craig; Standing, Susan; Gururajan, Raj; Fulford, Richard; Gengatharen, Denise
Abstract : Although telehealth has been used in the health sector for many years, there is still the perception that it is far from reaching its potential. Telehealth outcomes can be improved if knowledge is effectively managed, but this has proved complex to achieve in practice. Systems approaches that take a holistic view and address fundamental issues are likely to result in greater success than focusing solely on software systems. Managing knowledge in telehealth projects draws upon literature on knowledge management, team learning and virtual working. We report on the findings from interviews with telehealth professionals of their experiences and insights on managing knowledge. The major finding is that telehealth projects are functional in nature, focusing on patient diagnosis or training but rarely consider improving knowledge acquisition and sharing. We explain the reasons for this including the lack of understanding of knowledge management concepts that serve as a barrier to improvements. An integrated set of requirements for a telehealth knowledge management system is proposed that has potential to be a facilitator of change in this area. Copyright © 2016 John Wiley & Sons, Ltd.